Identifying adaptation effectiveness indicators using participatory approaches: A case study from the Gangetic Basin. (21st April 2019) - Mohan, Divya; Prabhakar, S.V.R.K.; Upadhyay, Himani
Abstract : Indicator-based approaches have been used extensively for measuring adaptation. Adopting participatory approaches helps in contextualizing the global level and generic indicators to suit the local-level conditions for measuring adaptation effectiveness. This paper discusses the application of a methodology for identifying a set of adaptation effectiveness indicators that could assist in prioritizing adaptation interventions. Using participatory approaches, the indicators were selected to assess the social, environmental and economic effectiveness of bunding as an adaptation option in the Gangetic Basin. The criteria for ranking of indicators were also determined along with an attempt to understand if there is an association between demographic factors and ranking of indicators by the respondents. The results showed that communities favoured the increase in fresh water availability as a measure for environmental effectiveness; food security for social effectiveness and farm income for economic effectiveness. The paper concludes by discussing the merits as well as limitations of using an indicator-based approach for assessing adaptation options.